LEGAL LANGUAGE OF THE LATIN LEGISLATIVE DOCUMENTS: FEATURES OF THE GENRE AND MAIN LINGUISTIC AND STYLISTIC CHARACTERISTICS - Kondaurova, Khrystyna (European Science, 2024)
The main purpose of the investigation is to differentiate key stylistic and genre characteristics of the legislative language of the Latin legeslative documents